2019
DOI: 10.1016/j.joca.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ultrasound in calcium pyrophosphate deposition disease of the knee joint

Abstract: Objective: To assess the diagnostic performance of ultrasound (US) for calcium pyrophosphate deposition (CPPD) at the level of menisci, hyaline cartilage (HC), tendons, and synovial fluid (SF) of the knee, and to examine inter-and intra-observer reliability. Design: We consecutively included patients with knee effusion over a 2-year period (43 patients with CPPD and 131 controls). All patients underwent SF analysis, conventional radiography (CR), and US examination using the Outcome Measures in Rheumatology (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…Так, в проводимых до настоящего времени популяционных исследованиях в качестве основного классификационного критерия использовались рентгенологические признаки ХК лучезапястных суставов, который, во-первых, не тождествен БДПК, а во-вторых, имеет довольно низкую чувствительность [0,29; 95% доверительный интервал (ДИ) 0,05-0,62] и специфичность (0,20; 95% ДИ 0,15-0,55) [13]. В целом чувствительность рентгенологически выявляемого ХК составляет примерно 40%, если брать в качестве эталона наличие кристаллов ПФК в СЖ [13][14][15][16]. Как следствие, эта оценка весьма приблизительна, поскольку 25-50% пациентов, у которых в СЖ выявляются кристаллы ПФК, не имеют рентгеновских признаков ХК коленных суставов [17].…”
Section: Discussionunclassified
“…Так, в проводимых до настоящего времени популяционных исследованиях в качестве основного классификационного критерия использовались рентгенологические признаки ХК лучезапястных суставов, который, во-первых, не тождествен БДПК, а во-вторых, имеет довольно низкую чувствительность [0,29; 95% доверительный интервал (ДИ) 0,05-0,62] и специфичность (0,20; 95% ДИ 0,15-0,55) [13]. В целом чувствительность рентгенологически выявляемого ХК составляет примерно 40%, если брать в качестве эталона наличие кристаллов ПФК в СЖ [13][14][15][16]. Как следствие, эта оценка весьма приблизительна, поскольку 25-50% пациентов, у которых в СЖ выявляются кристаллы ПФК, не имеют рентгеновских признаков ХК коленных суставов [17].…”
Section: Discussionunclassified
“…The peripheral portion of the MM must be carefully evaluated during the sonographic assessment of the TCL because pathological conditions involving the outer third of the medial fibrocartilage can clinically mimick ligamentous disorders. Parameniscal cysts, peripheral delaminations of the fibrocartilage (Dai et al, 2015; Dong et al, 2018), intra‐meniscal calcifications (Lee et al, 2019), meniscal extrusions (Chiba et al, 2020) and meniscal fragments migrating inside the superior/inferior parameniscal recesses (Ricci et al, 2020; 39: 805–810) are the most frequent conditions observed in clinical practice (Figure 7). As a side note, dynamic assessment may also be integrated to promptly evaluate hypo/hypermobility of the fibrocartilage (Video S12) (Karpinski et al, 2019; Reisner et al, 2020).…”
Section: Sonographic Examinationmentioning
confidence: 99%
“…Background US detection and quantification of inflammatory findings in the knee have been validated using MRI [129] and histology [130]. US has also shown great value in the detection of crystal deposition in several structures of the knee such as the articular cartilage, menisci, and tendons [131][132][133]. In OA, the assessment of meniscal protrusion, articular cartilage degeneration, synovitis, osteophytes, and Baker's cysts (popliteal cyst) are the main uses of US.…”
Section: Kneementioning
confidence: 99%